The impact of land degradation on agricultural productivity a multi-period economic land use model; a case study of the Neguev settlement, Costa Rica - Kuiper, M. (1997)
6 fig. 30 tab. 56 ref. También como: Field Report - Atlantic Zone Programme (CATIE) no. 165